PENGARUH KOMPENSASI MANAJEMEN BERBASIS SAHAM TERHADAP MANAJEMEN PAJAK PERUSAHAAN DENGAN MEMPERTIMBANGKAN FUNGSI PENGAWASAN KOMITE AUDIT - Wahyu Maulana Zulma, Gandy; Martani, Dwi (Program Studi Akuntansi FPEB UPI, 2015)
This study examines the relationship between stock-based compensation and audit committee on tax management at banking companies listed on BEI. The main purpose of this research is to test empirically whether stock-based compensation given can influence management's decision especially related to tax management, and to test indirect influence audit function of audit committee which is expected to weaken the relation between stock management compensation and tax management. The population used in this study is a banking company listed on the Indonesia Stock Exchange, using purposive sampling method obtained 22 companies with 128 samples of observations that meet the criteria. In testing the hypothesis using OLS Regression. The empirical test results show that the higher level of stock-based management compensation provided will further improve the corporate tax management, then audit committee activities within the company can prove weakening the relationship between stock-based management compensation and corporate tax management